Photoredox-Catalyzed Radical Relay Reaction Toward Functionalized Vicinal Diamines - An, Xiao-De; Yu, Shouyun (Synthesis, 2018)
A strategy has been described to synthesize β,γ-diaminoketones. This strategy is enabled by photoredox-catalyzed and nitrogen-centered radical-triggered cascade reactions of styrenes, enamides, and O-acylhydroxylamines in DMSO. Four bonds (one C–C, one C–N, and two C–O) are constructed in a single operation. Various functionalized vicinal diamines have been furnished by the radical relay reaction.
Keywords: photochemistry; ketones; nitrogen-centered radicals; cascade reactions; vicinal diamines